Hybrid evolutionary algorithms for the TSP - Minetti, Gabriela F. (2001)
Even if simply stated the travelling salesman problem (TSP) is one of the most studied NP-hard problems. Many algorithms have been proposed to solve TSP. Dynamic programming and branch and bound techniques provided the global optimum solution for the largest nontrivial instance of TSP with 7397 cities. However, 4 years of CPU time was required on a network of computers.